'n Funksionele denkbenadering in die verpleegkunde - A. Botes (AOSIS, 1991)
The aim of the functional approach is the application of knowledge to the solution of problems in nursing practice. In order to decide whether the functional approach is appropriate in nursing science it is necessary to study the relationship between nursing practice, nursing science and the philosophy of nursing science. If the functional approach seems appropriate, thought should be given to methodological implications for nursing research.